Bir Düşünce İnşa Etmek "Cumhuriyet Türkiyesi'nde Bir Mesele Olarak İslam"a Dair - (:unkn) unknown (My University, 2008)
Türkiye'de din-İslam meselesi ve bununla ilgili çevre meseleler merkezi bir tartışma alanı teşkil etmektedir. Fakat bu meselelerin anlaşılma/yorumlanma/ tartışılma seviye ve kapasitesi söz konusu olduğunda, meselelerin merkezi bir tartışma alanı teşkil etmesindeki kuvvet derecesinin ne yazık ki aynı seviyeye ulaşamadığı, hatta zaafa uğradığı görülmektedir. Bu makale, işaret edilen kuvvet ve zaaf durumları hakkında, İsmail Kara'nm bir süre önce yayınlanan "Cumhuriyet Türkiyesi 'nde Bir Mesele Olarak İslam" başlıklı kitabını merkeze alarak yapılan bazı değerlendirmeleri ihtiva etmektedir.

The problem of religion-Islam, with its correlations, no doubt provides a theme of central importance in Turkey. Comprehended, interpreted and debated in a way that befits the centrality of the problem, however, it is preponderantly not, marred with flaws more often than not inversely proportionate to the importance the matter indisputably boasts. Centering on the recently published work of Ismail Kara, "Cumhuriyet Türkiye'sinde Bir Mesele Olarak İslam/Islam As A Problem In The Republican Turkey", the paper will thus try its hand in offering some evaluations with respect to the pertinent flaws and strengths of frequent debates. First, the paper will seek to diagnose and critique the commonplace pedestrian levels, as is the case with many others in Turkey, concerning the comprehending, interpreting and debating of the problems perused throughout the pertinent work. Second, it will present, as an underlying reason for the pedestrian levels of comprehending, interpreting and debating the pertinent matters, blights again shared by many other cases in Turkey, the severance of the bonds between thought and life, attempting to delineate the principles whereby such bonds can be reinstated. The paper, which as a general approach acknowledges the importance of the work under scrutiny in terms of partaking in the proposed principles will finally describe and analyze the manner in which the problem of religion and Islam, with its subheadings, have been assessed by the work. Concluding the paper is the suggestion that the principles vied for at once constitute the very possibilities of establishing a profound thinking initiative, in general, of all matters of predicament, and in particular, the specific predicaments examined throughout the work.
To Construct a Thought "Islam as a Problem in the Republican Turkey"
Keywords: Felsefe